Maternal reactions to autonomous behaviors in toddlers in the context of different maternal representations - Dinler, Gökçe. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
The present study aims to investigate a sample of first-time mothers’ reactions to emerging autonomous behaviors in their toddlers in the context of different maternal representations. With this purpose, five mothers-of-sons and five mothers-ofdaughters who have a child of twelve to eighteen months of age from different socioeconomic backgrounds were interviewed. Thematic analysis method was used in the analysis of the semi-structured, in-depth interviews. Analysis of interviews yielded 4 themes regarding the mothers’ reactions to autonomous behaviors: (1) interpretation of autonomous behaviors in toddlers, (2) subjective assessment of caregiving to an increasingly autonomous toddler, (3) maternal emotional reactions, and (4) maternal behavioral reactions. Furthermore, analysis of mothers’ narrations indicated three types of maternal representations: Connected-Autonomous, Connected-Non-Autonomous, and Non-Connected. Mothers with different types of maternal representations displayed slight differences in their emotional and behavioral reactions to autonomous behaviors in their toddlers. While mothers with Connected-Autonomous representations reported generally positive emotions and autonomy supportive behaviors; mothers with Connected-Non-Autonomous representations reported higher levels of ambivalent emotions and considerable amount of autonomy supportive behaviors with some controlling behaviors in certain contexts. Lastly, mothers with Non-Connected representations reported limited affective and behavioral engagement with their toddlers.
Keywords: Motherhood.; Mother and child.